Pattern of Pediatric Inguinal Hernia Repairs in Our Hospital Over the Last 5 Years - Fayyaz, Muhammad; Usman Akram, Muhammad; Aslam, Hammad; Hussain, Abid; Ahmad, Khadija; Khan, Sibghatullah (Journal of Neonatal Surgery, 2024)
Background:Inguinal hernia is one of the most common surgical conditions in children, accounting for a significant proportion of pediatric operations. Patterns of presentation and outcomes may vary by age, sex, laterality, and evolving surgical practice. This study aimed to evaluate the demographic profile, clinical characteristics, operative patterns, and postoperative outcomes of pediatric inguinal hernia repairs performed over the last five years in this hospital. Methods:A retrospective descriptive study was conducted on 70 pediatric patients who underwent inguinal hernia repair between January 2023 and January 2024 at Jinnah hospital Lahore. Data were collected from hospital records, including demographic details, hernia type, side, mode of presentation, surgical technique, and postoperative complications. Statistical analysis was performed using SPSS version 25.0, with a p-value < 0.05 considered significant. Results:Most children were males (85.7%) with a mean age of 4.8 ± 3.2 years. The right side was predominantly affected (68.6%), and the indirect type of hernia was most common (97.1%). Open herniotomy remained the preferred approach (85.7%), while laparoscopic repair showed a gradual increase in frequency. Mean hospital stay was 1.6 ± 0.8 days. Complications were minimal, including wound infection (4.3%), scrotal edema (4.3%), and recurrence (2.9%). Conclusion:This study demonstrated that pediatric inguinal hernia continues to predominantly affect males and the right side, with low recurrence and complication rates following both open and laparoscopic repair. The increasing adoption of minimally invasive surgery reflects evolving pediatric surgical practice, emphasizing safety and early recovery